Pengembangan Usaha Pesantren Sirajussa’adah Berbasis Manajemen - Siwi Nugrahaeni; Alfida Aziz; Henni Nastiti (Universitas Persada Indonesia YAI, 2023)
This Community Service is carried out at the Sirajus'Saadah Islamic Boarding School, which aims todevelop the business so that income increases through the application of management.. This activity usestwo approaches, namely the counseling approach and the mentoring / coaching approach. The counselingapproach includes: 1) financial management training, 2) risk management training, 3) productionmanagement training, while the increase in mentoring / training includes: 1) assistance in determiningoptimal working capital needs, 2) assistance in the preparation of cost of goods produced / cost of goodssold 3) Assistance in mitigating business risks. The target activity and the desired output of this communityservice is an article published through journals with ISSN or proceedings with ISBN from national seminarsand to provide solutions to business managers at the Sirajus'Saadah Islamic boarding school so that themanaged business can experience development and sales growth as well as increased income, Before theimplementation of the abdimas is carried out, business managers are asked to fill out questionnaires aboutworking capital, cost of goods produced, determination of selling prices and business risks. At the end of thetraining, an evaluation will be carried out to find out their understanding, about the counseling that has beencarried out by the service team, and then mentoring / training is carried out by applying the material that hasbeen given to the businesses they manage, it is hoped that the results of the evaluation of their understandingincrease to 95% and practice the businesses they manage.